Sites of Translation: What Multilinguals Can Teach Us about Digital Writing and Rhetoric - Gonzales, Laura (Sweetland Digital Rhetoric Collaborative, 2018)
Winner of the 2016 Sweetland Digital Rhetoric Collaborative Book Prize Sites of Translation illustrates the intricate rhetorical work that multilingual communicators engage in as they translate information for their communities. Blending ethnographic and empirical methods from multiple disciplines, Laura Gonzales provides methodological examples of how linguistic diversity can be studied in practice, both in and outside the classroom, and provides insights into the rhetorical labor that is often unacknowledged and made invisible in multilingual communication. Sites of Translation is relevant to researchers and teachers of writing as well as technology designers interested in creating systems, pedagogies, and platforms that will be more accessible and useful to multilingual audiences. Gonzales presents multilingual communication as intellectual labor that should be further valued in both academic and professional spaces, and supported by multilingual technologies and pedagogies that center the expertise of linguistically diverse communicators.